Comparative systematic review and meta-analysis of reactogenicity, immunogenicity and efficacy of vaccines against SARS-CoV-2 - Ian McDonald (Nature Portfolio, 2021)
Abstract As SARS-CoV-2 vaccines are deployed worldwide, a comparative evaluation is important to underpin decision-making. We here report a systematic literature review and meta-analysis of Phase I/II/III human trials and non-human primates (NHP) studies, comparing reactogenicity, immunogenicity and efficacy across different vaccine platforms for comparative evaluation (updated to March 22, 2021). Twenty-three NHP and 32 human studies are included. Vaccines result in mostly mild, self-limiting adverse events. Highest spike neutralizing antibody (nAb) responses are identified for the mRNA-1273-SARS-CoV and adjuvanted NVX-CoV2373-SARS-CoV-2 vaccines. ChAdOx-SARS-CoV-2 produces the highest T cell ELISpot responses. Pre-existing nAb against vaccine viral vector are identified following AdH-5-SARS-CoV-2 vaccination, halving immunogenicity. The mRNA vaccines depend on boosting to achieve optimal immunogenicity especially in the elderly. BNT162b2, and mRNA-1273 achieve >94%, rAd26/5 > 91% and ChAdOx-SARS-CoV-2 > 66.7% efficacy. Across different vaccine platforms there are trade-offs between antibody binding, functional nAb titers, T cell frequency, reactogenicity and efficacy. Emergence of variants makes rapid mass rollout of high efficacy vaccines essential to reduce any selective advantage.